Partisipasi Siswa Dalam Meningkatkan Mutu Pembelajaran Pendidikan Agama Islam Di Sekolah Dasar Islam Al-Hidayah Banjarmasin - Anggra Wati Sulistya Ningsih (Integrated Education Journal, 2024)
The demands on graduates of educational institutions are increasingly pressing. In addition to competition between educational institutions, educational institutions must also meet minimum graduation standards. This research uses a qualitative approach using data collection techniques, observation, interviews and documentation. Based on the findings, the author concludes as follows: Strategy for Improving the Quality of Education at SDI Al - Hidayah Sungai Banjarmasin city and in the input aspect the strategy adopted is the selection of Human Resources through a strict selection process in accordance with predetermined criteria; the procurement of infrastructure is very complete; partnership support through collaboration with school committees as well as foundations and related educational institutions; guarantee of financing obtained from stakeholders and integration of the national curriculum, integrated Islamic school network and local foundations. In the aspect of the strategic process carried out, namely optimization